The Development of an Equine Fracture Documentation System - Fackelman, G. E.; Peutz, I. P.; Norris, J. C.; Auer, J. A.; Rechenberg, von B. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Due to a perceived need for better information on the occurrence and repair of equine fractures, we developed a system designed to gather data on an interinstitutional basis. Fundamental to our task was the creation of a system of classifying the injuries most commonly treated by internal fixation, but including other fracture forms as well.The initial ("paper") documentation system, designed along the lines of the existing AO/ASIF Human format was praised by pilot study participants for its thoroughness and relevance, but individual clinician compliance was low due to the system’s length and complexity. The present ("diskette") version was designed for use with the Apple Macintosh, and was later modified for IBM PCs and their clones. It is currently being distributed to participating AO/ASIF Vet member clinics. The AO/ASIF EFDS was designed with a view toward crossover with existing human and developing small animal systems. As such it should provide an important building block for efforts in veterinary comparative orthopedics and traumatology.The need for a classification of commonly occurring equine fractures was recognized, and a corresponding system developed. Originally conceived on paper with computer-readable sheets, the system was later modified to be committed to diskettes. In its current form, the system is in use documenting the outcome of repair of exercise induced fractures. Updates will incorporate other (e.g. long bone) fractures, and long-term follow-up data.
Keywords: Fracture; equine; horse; documentation; classification; case records